Correlates of Spirituality among African American and Black Caribbean Emerging Adults - Meredith O. Hope; Ann W. Nguyen; Robert Joseph Taylor; Linda M. Chatters (Religions, 2024)
Spirituality is a significant cultural strength and resource for Black emerging adults. Numerous studies show that increasing numbers of emerging adults tend to identify themselves as being spiritual but not religious. However, no studies to date have identified the demographic correlates of spirituality for Black emerging adults from different ethnic groups (i.e., African American and Black Caribbean). Data from the National Survey of American Life were used to identify the demographic correlates of two indicators of spirituality (e.g., self-rated spirituality and subjective spirituality) among African American and Black Caribbean emerging adults using linear regression. For African Americans, being a woman predicted both greater self-rated spirituality and subjective spirituality. However, among Black Caribbeans, men rated spirituality higher in importance than women. African Americans who reported higher educational attainment tended to report higher levels of self-rated spirituality and subjective spirituality. Romantic status for Black Caribbeans, whether they had no romantic involvement or a current romantic partner, was associated with lower self-ratings of spirituality. Unmarried cohabitating individuals in both ethnic groups tended to report lower levels of self-related spirituality. Unemployment for Black Caribbeans was associated with lower subjective spirituality. Findings are of interest to those who serve and work with Black emerging adults.